Reflection of reality in protophilosophical forms of ideology (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2024)
In the article, unique proto-philosophical forms of ideology are reflected in the context of social existence, default worldview, mythology and religious-mythical knowledge. The essence of the translation function of proto-philosophical forms of ideology is revealed, since ideas that include social relations and structure are compatible with other elements of social consciousness.
Keywords: Ideology, proto-philosophy, transmission, diochronic, synchronic relationships, spiritual heritage, tradition, ritual, illusion, faith, allegory, utopia, artistic image